Terrorism and policy relevance critical perspectives - Fitzgerald, James 1984-; Ali, Nadya; Armstrong, Megan (Megan A.) (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2018)
Articles drawn from papers presented at a workshop "10 Years of Critical Terrorism Studies" and a conference "Critical Terrorism Studies and Policy Relevance" organized by the Critical Studes on Terrorism Working Group of the British International Studies Association (BISA), held at the BISA Annual Conference in London, 15 June 2015, and the University of Leeds, 3-4 September 2015, respectively